Conference between the Prime Minister and representatives of the Miners' Federation of Great Britain, 15 April 1926 (page 5)
1926-05-15 "Conference between the Prime Minister and representatives of the Miners' Federation of Great Britain, 15 April 1926 (page 5)" [g0426005.jpg], 15 April 1926, Miners' Federation of Great Britain